An xa5 Resistance Gene-Breaking Indian Strain of the Rice Bacterial Blight Pathogen Xanthomonas oryzae pv. oryzae Is Nearly Identical to a Thai Strain - Carpenter, Sara C. D.; Mishra, Prashant; Ghoshal, Chandrika; Dash, Prasanta K.; Wang, Li; Midha, Samriti; Laha, Gouri S.; Lore, Jagjeet S.; Kositratana, Wichai; Singh, Nagendra K.; Singh, Kuldeep; Patil, Prabhu B.; et al. (Frontiers in Microbiology, 2020)
The rice bacterial blight pathogen Xanthomonas oryzae pv. oryzae (Xoo) constrains production in major rice growing countries of Asia. Xoo injects transcription activator-like effectors (TALEs) that bind and activate host ‘susceptibility’ (S) genes important for disease. The bacterial blight resistance gene xa5, which reduces TALE activity generally, has been widely deployed. However, strains defeating xa5 have been reported in India and recently also in Thailand. We completely sequenced and compared the genomes of one such strain from each country and examined the encoded TALEs. The two genomes are nearly identical, including the TALE genes, and belong to a previously identified, highly clonal lineage. Each strain harbors a TALE known to activate the major S gene SWEET11 strongly enough to be effective even when diminished by xa5. The findings suggest international migration of the xa5-compatible pathotype and highlight the utility of whole genome sequencing and TALE analysis for understanding and responding to breakdown of resistance.